PENINGKATAN PEMAHAMAN KONSEP PENGUKURAN BERAT MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA KONKRET PADA SISWA KELAS II - Aprilia, Reza; Denna Delawanti Chrisyarani; Tumijan; Indah Sukowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low understanding of weight measurement among second-grade students at SDN Pisangcandi 2 Malang City, particularly in distinguishing and ordering objects based on their weight. This study aimed to improve students’ conceptual understanding through the implementation of the Contextual Teaching and Learning (CTL) approach assisted by concrete media. This research employed a Classroom Action Research (CAR) design conducted in two cycles involving 28 students as research subjects. Data collection techniques included tests, observations, interviews, and documentation. The collected data were analyzed using the Miles and Huberman model through the stages of data collection, data reduction, data display, and conclusion drawing. The results showed an improvement in students’ conceptual understanding, indicated by an increase in the average score from 57.14 in the pre-cycle to 65.85 in Cycle I and 84.68 in Cycle II, as well as an increase in learning mastery from 36% to 50% and 82.14%. This improvement occurred because students learned through direct experiences in comparing and ordering objects using concrete media. Therefore, the implementation of CTL assisted by concrete media was effective in improving second-grade students’ understanding of weight measurement concepts.